Esmolol as an adjunct to general balanced anaesthesia in neurosurgery - Lončar-Stojiljković, Dragana B.; Maksimović, Žana; Djuric, Marko (Scripta Medica, 2021)
Background / Aim: In surgery, and especially in the neurosurgical operations, maintenance of cardiovascular stability during and in the phase of the immediate postoperative recovery is of vital importance. The aim of this study was to investigate the effects of continuous esmolol infusion on the values of cardiovascular parameters and quality of the emergence from anaesthesia in neurosurgical patients. Methods: A total of 40 patients of both sexes scheduled for elective supratentorial surgery were randomly assigned to two groups. Esmolol group received intravenous (iv) infusion of esmolol esmolol dissolved in 5 % glucose solution (during the first 5 min at a rate of 0.3 mg/kg/min and thereafter at a rate of 0.1 mg/kg/min), while the ones from the control group received a 5 % glucose solution without esmolol at the same volume and rate. Cardiovascular parameters were registered at critical phases of anaesthesia and operation (induction, intubation, placement of Mayfield frame, craniotomy, skull closure, extubation). Recovery after anaesthesia was assessed based on times of eye opening on command, spontaneous eye opening and regaining of full orientation. Results: Values of systolic blood pressure and heart rate were significantly lower in the esmolol than in the control group of patients. Although the duration of anaesthesia did not differ, patients from the esmolol group required significantly less opioids and isoflurane and recovered after the anaesthesia significantly faster than the patients in the control group. Conclusion: Ultrashort-acting beta-adrenergic receptor antagonist esmolol, administered as a continuous iv infusion, assures better cardiovascular stability and smoother emergence from the balanced inhalation general anaesthesia than the control glucose infusion in elective neurosurgical patients.